KASB-HUNAR NOMLARINING JAMIYAT HAYOTIDA TUTGAN O’RNI INGLIZ XALQI MISOLIDA - Kulmuhamedova Lobar; Erdanova Zebo Abulkasimovna (Journal of new century innovations, 2023)
Annotation: This article is about the role of professional names in the life of English people, and the reader will have a vivid impression of the culture of the English nation and get a lot of knowledge about the country under study.